Effect of drill string rotation on the dynamic response of drilling risers - Major, Igoke E.; Big-Alabo, Akuro; Odi-Owei, Steven (Zielona Góra: Uniwersytet Zielonogórski)
The effect of the rotation of a drill string on the response of a drilling riser has been studied. A governing equation for the flexural response that incorporates the effect of the drill string rotation is developed from first principles, and the resulting differential equation is found to have a variable coefficient, which is a function of the drill string rotational speed. Results simulated for the free vibration response show that the drill string rotation reduces the natural frequency and increases the amplitude of vibration of the drilling riser.
Keywords: drilling riser; drill string; drill string rotational speed; free vibrations; threshold rotational speed